Whose Error Anyway? Epigraphic and Orthographic Variation in a Book of the Earth as Evidence for Multiple Master Documents in the Sarcophagus Chamber of Ramesses VI - Roberson, Joshua Aaron.
This article considers instances of variation among determinatives within the so-called “Book of the Earth,” as attested in the burial chamber of Ramesses VI. Variants that appear to occur as deliberate contrivances of the ancient authors are distinguished from those that might have arisen as a result of scribal error. The occurrence of variants with thematic or mythological significance and their clustering within the three dimensional space of the burial chamber are then evaluated as evidence for the use of master document(s), which have otherwise been lost, in the execution of the monument’s decorative program. http://dx.doi.org/10.5913/jarce.55.2019.a010